Limitations for Reliable Operation at Elevated Temperatures of Al2O3/AlGaN/GaN Metal–Insulator–Semiconductor High‐Electron‐Mobility Transistors Grown by Metal‐Organic Chemical Vapor Deposition on Silicon Substrate. Issue 7 (20th November 2019) - Heuken, Lars; Ottaviani, Alessandro; Fahle, Dirk; Zweipfennig, Thorsten; Lükens, Gerrit; Kalisch, Holger; Vescan, Andrei; Heuken, Michael; Burghartz, Joachim N.
Abstract : Herein, the gate degradation mechanisms of gallium nitride (GaN)‐based metal–insulator–semiconductor high‐electron‐mobility transistors (MISHEMTs) utilizing Al2 O3 grown by plasma‐enhanced atomic layer deposition (PEALD) are systematically investigated. By applying constant voltage stress and the time‐dependent dielectric breakdown (TDDB) methodology under variation of bias and temperature, an activation energy of 1.25 eV for the time to breakdown and a 1/ E model extrapolating the lifetime are found. A maximum gate operation voltage at 298 K of 4.9 V is extrapolated, which decreases to a projected voltage of 3.5 V at 598 K operation temperature, due to an accelerated defect generation. The physical origin of the TDDB of Al2 O3 is related to the formation of a percolation path by randomly generated defects in the oxide under stress bias. This mechanism, which also requires the presence of an initial defect density in Al2 O3, is confirmed by Monte Carlo simulations, which are in agreement with the experimental data. Abstract : The gate degradation mechanisms of gallium nitride (GaN)‐based metal–insulator–semiconductor high‐electron‐mobility transistors (MISHEMTs) utilizing Al2 O3 grown by plasma‐enhanced atomic layer deposition (PEALD) are systematically investigated. By applying constant voltage stress and the time‐dependent dielectric breakdown methodology under variation of bias and temperature, the activation energy of the time to breakdown is found and the lifetime is extrapolated.